DIGITALISASI ARSIP FOTO UNIVERSITAS DIPONEGORO SEBAGAI LANDASAN IMPLEMENTASI KEBIJAKAN KETERBUKAAN INFORMASI PUBLIK - Handayani, Tri; Kurniawan, Amin Taufiq (Faculty of Humanities, Diponegoro University, 2015)
This paper focuses on digitalization archival photo Diponegoro University, as the basis for Diponegoro University towards the era of public information openness. This basis can be realized among others bythe publication digital photo archives of the three traditional missions of academic institutions (tridharma perguruan tinggi)Â andÂ digital photo archive of administrative activity of Head of the University of Diponegoro through the website of Khazanah Arsip Foto Undip (Collection of Undip Photo Archive). As a conclusion, Khazanah Arsip Foto Undip were digitalized and uploaded to the Undip website were information to the public about the achievements of the University of Diponegoro in organizing the three traditional missions of academic institutions activities, and the information to the public about the achievements of the Head of Diponegoro University policy.